Comparison of clinical effects and patient satisfaction between ultra-pulsed CO₂ laser treatment and surgical excision in patients with facial basal cell carcinoma - Chen, An-Chen; Zheng, Chen; Jian, Qi-Chao; Zhang, Peng (Frontiers in Surgery, 2025)
BackgroundBasal cell carcinoma (BCC) commonly affects facial skin, with surgical excision being the usual treatment. However, surgery often leads to complications and slow healing, impacting quality of life. Recently, ultra-pulsed CO₂ laser has emerged as a minimally invasive option with good cosmetic results, but its effectiveness and patient satisfaction compared to surgery are still uncertain.ObjectiveThis study aims to compare the clinical outcomes and patient satisfaction between ultra-pulsed CO₂ laser treatment and surgical excision for patients with facial BCC.MethodsA retrospective analysis was conducted on 100 patients with facial BCC treated at our dermatology department from January 2021 to January 2024.Among them, 50 patients received ultra-pulsed CO₂ laser treatment, while 50 underwent traditional surgical excision. We compared the tumor excision rates, incidence of postoperative complications, healing times, and patient satisfaction (assessed through a questionnaire) between the two groups.ResultsThe clinical effective rate in the ultra-pulsed CO₂ laser group was 94.0%, compared to 90.0% in the surgical excision group, with no statistically significant difference between the two groups (p > 0.05).Postoperative complications in the CO₂ laser group were primarily mild burns and inflammatory erythema, all of which resolved spontaneously within 1–2 days without treatment, with no serious adverse reactions reported. Recurrence rates were 4.00% (laser) vs. 16.00% (surgery), the difference between the two groups was statistically significant (p < 0.05). Regarding pain scores, there was no significant difference in preoperative pain scores between the groups; however, the CO₂ laser group reported significantly lower pain scores at 1, 3 days and 7days postoperatively (P < 0.001). Furthermore, patient satisfaction was significantly higher in the CO₂ laser group compared to the surgical group (96.0% vs. 76.0%, P < 0.001).ConclusionIn summary, both ultra-pulsed CO₂ laser treatment and surgical excision exhibit similar clinical efficacy in the management of facial basal cell carcinoma. Nonetheless, ultra-pulsed CO₂ laser treatment offers notable benefits regarding postoperative complication rates, pain scores, and patient satisfaction. Consequently, ultra-pulsed CO₂ laser treatment may be regarded as an effective and patient-friendly alternative for the treatment of facial basal cell carcinoma.